'A different ball game': responsive capacity strengthening for generalist occupational therapists delivering hand rehabilitation in the public sector. - van Stormbroek, Kirsty; Myezwa, Hellen; O'Brien, Lisa; Rauch van der Merwe, Tania (South African Journal of Occupational Therapy, 2026)
Introduction: Generalist occupational therapists provide hand rehabilitation in challenging settings due to the scarcity of specialist hand therapists. This study aimed to describe the experiences of generalist occupational therapists in South Africa to identify their support and development needs, and propose interventions to address these. Methods: This qualitative descriptive instrumental case study design involved six purposively sampled occupational therapists delivering hand therapy in a generalist capacity. Data from in-depth interviews and fieldnotes were analysed using reflexive thematic analysis. Within- and cross-case analysis was undertaken. Findings: Vignettes illustrate within-case findings and cross-case analysis generated five themes: participants' experienced hand rehabilitation as both stressful and satisfying and engaged in a distinct learning journey. To respond to the demand for hand therapy, participants articulated various enablers, captured in rising to the challenge. traversing system and service change explains the complex and transient nature of the systems and services in which participants functioned. Finally, once upon a hand injury illustrates the lived realities of patients and the practice complexities that therapists navigate. Conclusion: Capacity strengthening that is responsive to generalist occupational therapists' experiences and needs should include individual-level strategies, team and human resource strategies, education, physical resources, and system and service-level strategies. Implications for practice * Delivering hand rehabilitation as a generalist occupational therapist in the public sector is both stressful and satisfying, and a learning journey situated within a dynamic health system and influenced by the realities of patients' lives. * Capacity strengthening to support this cadre of therapists should include education, physical resources and strategies that target the individual; the team and human resources; and system and service-level strategies.